Synchronous mucinous metaplasia and neoplasia of the female genital tract with both pulmonary metastases and STK11/KRAS gene mutations: a case report - Wang, Ru; Yu, Hao; Liu, Ming; Hao, Ting; Wang, Xiangyu; Cao, Lianbao (Frontiers in Oncology, 2023)
First reported and described by Mikami in 20091, synchronous mucinous metaplasia and neoplasia of the female genital tract (SMMN-FGT) is characterized by several morphological changes in two or more sites of concurrent multifocal mucinous lesions in the female genital tract, including non-neoplastic, benign, junctional, and malignant features. Seldom is the condition described, and there is no consensus regarding its frequency, clinical presentation, pathological characteristics, diagnosis, treatment, or prognosis. In this case report, we describe an SMMN-FGT patient who also had lung metastases and STK11/KRAS gene mutations.